1167 Nursing Perceptions of Sleep Assessment in the Intensive Care Unit. (27th May 2020) - Heavner, M S; Jobe, S L; Hurley, J; Le, B; Kantner, C; Heavner, J J; Shanholtz, C; Verceles, A; Wickwire, E M
Abstract: Introduction: Sleep disruption in intensive care unit (ICU) patients is highly prevalent and may contribute to adverse clinical outcomes. Although clinical practice guidelines recommend routine assessment of sleep, surveys of ICU clinicians indicate that sleep assessment programs (SAP) are rarely implemented. The purpose of the current project was to characterize sleep-related perceptions, practices, and knowledge among ICU nurses, to identify barriers and facilitators of implementation of a systematic SAP. Methods: A 29-item, paper-based survey was administered to all nurses (N=220) in a medical ICU at a 750-bed academic medical center and a mixed ICU in a 300-bed community hospital. Voluntary survey completion was conducted over four weeks. Descriptive statistics were employed. Results: A total of 163 surveys were completed (74.1%). Participants were primarily female (n=135; 82.8%), day-shift nurses (n=83; 50.9%), with 2-5 years of ICU experience (n=70; 42.9%). Respondents said they sometimes (n=52; 31.9%), and often (n=52; 31.9%), assess sleep, and 76.1% (n=124) reported not assessing sleep formally in the last three shifts. Approximately half of the respondents (n=85; 52.1%) were not aware of clinical practice guideline recommendations for sleep in the ICU. Most nurses reported that their unit could benefit from a SAP (n=101; 62.0%) and that they should have a primary responsibility in ensuring that sleep is discussed daily (n=144; 88.3%). Conclusion: Despite published guidelines recommending routine sleep assessment, ICU nurses report infrequent assessment and a lack of awareness of these guidelines. However, ICU nurses believe implementation of routine sleep assessments would be beneficial to patient care. This suggests that SAP implementation would be positively received by ICU nurses. Future studies evaluating knowledge and site-specific perceptions and practices, as well as nursing staff characteristics, can further guide implementation of SAPs in the ICU. Support: